Initial clinical experience performing sialendoscopy for salivary gland protection in patients undergoing 225Ac-PSMA-617 RLT - Rathke, Hendrik; Kratochwil, Clemens; Hohenberger, Ralph; Giesel, Frederik L.; Flechsig, Paul; Plinkert, Peter K.; Haberkorn, Uwe; Bulut, Cem (European journal of nuclear medicine and molecular imaging, 2019)
PurposeThe main side effect of prostate-specific membrane antigen targeting alpha therapy (PSMA TAT) is dry mouth syndrome. Inflammation of the salivary glands and consequent reduced salivary function have been reported in patients after radioiodine therapy. The beneficial effects of sialendoscopy on radiation-induced inflammation in tissue are well known. Thus sialendoscopy with dilatation, saline irrigation and steroid injections (prednisolone) was performed before and after 225Ac-PSMA-617 TAT to reduce inflammatory effects in the salivary glands and to improve or prevent xerostomia.MethodsEleven men with metastatic castration-resistant prostate cancer (mean age 68.5 years, range 58-80 years) underwent sialendoscopy, dilatation, saline irrigation and steroid injection of both submandibular and both parotid glands before or after every cycle of 225Ac-PSMA-617 TAT. Sialendoscopy and steroid injection were performed by a senior ENT physician. Quality of life was evaluated using two health-related quality of life (HRQOL) questionnaires, the Xerostomia Questionnaire (XQ) and the Xerostomia Inventory (XI) before and 3 months after the intervention.ResultsIn all 11 patients both parotid and both submandibular glands were affected by radiation sialadenitis and sialendoscopy was performed. The patients experienced no complications after sialendoscopy, and showed a significant improvement in HRQOL as measured using the XQ and XI. After sialendoscopy the XQ score decreased significantly from 77.7 ± 13.6 to 42.7 ± 14.8 (p = 0.003) and the XI score decreased from 44.5 ± 6.9 to 25.8 ± 12.8 (p = 0.003). Due to the limited number of patients we only report tendencies.ConclusionSialendoscopy with dilatation, saline irrigation and steroid injection had beneficial effects on salivary gland function and HRQOL in patients undergoing 225Ac-PSMA-617 RLT. However, even with sialadenoscopic support after multiple cycles of TAT, salivary gland function was reduced and xerostomia was present. Therefore, not only inflammation but also the direct effect of radiation is a putative cause of dry mouth. Further research is necessary to determine the main side effects of PSMA TAT.
First onine: 27 August 2018
Im Titel ist 225 hochgestellt
Gesehen am 29.04.2019